Averaged capture cross sections and radiative strength functions in pf-shell nuclei - Nemashkalo, B.A.; Storizhko, V.E. (Вопросы атомной науки и техники, 2003)
The paper presents experimental results from proton capture reactions by nuclei ⁴⁵Sc, ⁴⁸,⁵⁰Ti, ⁶⁰,⁶¹,⁶²,⁶⁴Ni, ⁶³,⁶⁵Cu, ⁵⁶,⁵⁸Fe, ⁶⁶,⁶⁸Zn, ⁶⁹Ga, ⁷²,⁷⁴Ge, and ⁷⁶,⁷⁸Br, namely, partial cross sections and radiative strength functions (RSF) simulated in the framework of a statistical model and new phenomenological approaches to the description of the RSF developed by Kadmensky, Sirotkin, and Plujko. Data for the reactions ⁶³,⁶⁵Cu(р,g) ⁶⁴,⁶⁶Zn are original. The measurements were performed in NSC KIPT using a Van de Graaf accelerator for 4.5 MeV. The RSFs were determined so as to achieve the best agreement between the measured and the calculated cross sections for fixed global parameters of the statistical model. The measured RSF values are model-dependent. As was found, the RSF is influenced by the excitation energy and final state properties of nuclei, contrary to Brink’s hypothesis that denies the relationship between the RSF and the nuclear structure. These results can be extended to all pf-shell nuclei.